Penggunaan model pembelajaran dengan pendekatan konstruktivisme untuk meningkatkan kemampuan berpikir kritis matematis peserta didik SMK Bina Putera Nusantara Jurusan Farmasi - Eva Mulyani (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2015)
This study aims to determine the enhancement in the ability of mathematical critical thinking of students treated by Constructivism Learning Approach and direct learning, to know the difference enhancement in the ability of mathematical critical thinking of students in upper, middle and lower group treated by Constructivism Learning Approach and direct learning. This is an experimental study. The population are students of SMK Bina Putera Nusantara (BPN) Department of Pharmacy Class XI and were chosen two classes randomly, Class Pharmacy III (F-III) and Pharmacy IV (F-IV).  The experiment class was treated using constructivism learning approach, and the control class was treated using direct learning. The instruments used in this study were test of the ability of mathematical critical thinking and observation sheet. Data analysis used were t test and two-way ANOVA also Contingency Coefficient. Based on the results analysis, it shows that the enhancement in the ability of mathematical critical thinking of students through constructivism learning approach is better than the enhancement in the ability of mathematical critical thinking of students through direct learning. There is different enhancement in the ability of mathematical critical thinking between upper, middle and lower group.